Chronic constriction injury-induced nociception is relieved by nanomedicine-mediated decrease of rat hippocampal tumor necrosis factor. Issue 7 (July 2015) - Gerard, Elizabeth; Spengler, Robert N.; Bonoiu, Adela C.; Mahajan, Supriya D.; Davidson, Bruce A.; Ding, Hong; Kumar, Rajiv; Prasad, Paras N.; Knight, Paul R.; Ignatowski, Tracey A.
Abstract : Abstract: Neuropathic pain is a chronic pain syndrome that arises from nerve injury. Current treatments only offer limited relief, clearly indicating the need for more effective therapeutic strategies. Previously, we demonstrated that proinflammatory tumor necrosis factor-alpha (TNF) is a key mediator of neuropathic pain pathogenesis; TNF is elevated at sites of neuronal injury, in the spinal cord, and supraspinally during the initial development of pain. The inhibition of TNF action along pain pathways outside higher brain centers results in transient decreases in pain perception. The objective of this study was to determine whether specific blockade of TNF in the hippocampus, a site of pain integration, could prove efficacious in reducing sciatic nerve chronic constriction injury (CCI)-induced pain behavior. Small inhibitory RNA directed against TNF mRNA was complexed to gold nanorods (GNR-TNF siRNA; TNF nanoplexes) and injected into the contralateral hippocampus of rats 4 days after unilateral CCI. Withdrawal latencies to a noxious thermal stimulus (hyperalgesia) and withdrawal to innocuous forces (allodynia) were recorded up to 10 days and compared with baseline values and sham-operated rats. Thermal hyperalgesia was dramatically decreased in CCI rats receiving hippocampal TNF nanoplexes; and mechanical allodynia was transiently relieved. TNF levels (bioactive protein, TNF immunoreactivity) in hippocampal tissue were decreased. The observation that TNF nanoplex injection into the hippocampus alleviated neuropathic pain-like behavior advances our previous findings that hippocampal TNF levels modulate pain perception. These data provide evidence that targeting TNF in the brain using nanoparticle-protected siRNA may be an effective strategy for treatment of neuropathic pain. Abstract : Selectively decreasing tumor necrosis factor-alpha production exclusively in the contralateral hippocampus of rats with sciatic nerve chronic constriction injury alleviates neuropathic pain behaviors.